Halolactonization of N-Acyl-N-(2-cyclohex-1-en-1-yl-6-methylphenyl)glycines: Towards Production of 4,1-Benzoxazoheterocycles - Gataullin, Rail R. (Synthesis, 2023)
A significant influence of the nature of the acyl substituent at the nitrogen atom on the direction of the reaction in the interaction of N-acyl-N-(2-cyclohex-1-en-1-yl-6-methylphenyl)glycines with bromine was found. In the case of the N-benzoyl derivative, along with benzoxazocinone, which is formed through the stages of pseudoallyl halogenation and subsequent lactonization due to the replacement of the bromine atom by the oxygen atom of the carboxyl group, a mixture of axially chiral isomers of spiro-fused 2′-bromocyclohexane-benzoxazepin-3-ones was also obtained. The aR*,R*,R*-isomer of benzoxazepinone, which initially is four times predominant in the reaction mixture, upon dissolution in deuterochloroform, slowly transforms into aS*-conformer until a ratio of 2:1 is established. In the case of the N-acetyl analogue of this glycine, the only heterocycle is the product of 7-exo-halogenlactonization, the benzoxazepinone spiro-fused with 2′-bromocyclohexane and an undetermined configuration of the axial chirality.
Keywords: benzoxazepinone; halolactonization; atropisomer; glycine; benzoxazocinone; axial chirality